Handbook of Polymers in Medicine - Mozafari, Masoud; Mozafari, Masoud; Singh Chauhan, Narendra Pal (Woodhead Publishing, 2023)
Handbook of Polymers in Medicine combines core concepts and advanced research on polymers, providing a better understanding of this class of materials in medicine. The book covers all aspects of medical polymers from characteristics and biocompatibility, to the diverse array of applications in medicine. Chapters cover an introduction to polymers in medicine and the challenges associated with biocompatibility in human tissue, polyurethane and supramolecular polymers and their specific applications in medicine, from tissue regeneration to orthopedic surgery and cancer therapeutics. This book offers an interdisciplinary approach that will appeal to researchers in a range of disciplines, including biomedical engineering, materials science, chemistry, pharmacology and translational medicine. The book will also make a useful reference for clinicians and those in medical fields who are interested in materials for medical applications, as well as R&D groups involved in medical device design. - Systematically covers individual polymer classes, from characteristics and biocompatibility to applications in biomedicine - Covers a broad range of applications in medicine, such as cardiac tissue engineering, targeted drug delivery, dentistry, and more - Provides an interdisciplinary review of polymers in medicine, allowing advanced students and experienced researchers in a range of biomedical and clinical fields to learn more about this fast-evolving area